Peningkatan Derajat Kesehatan dan Gizi Remaja Putri melalui Penyuluhan Kesehatan Reproduksi dan Gizi (Penerapan media Video Pembelajaran Berbasis Penelitian) - Febriana, Rina; Yulianti, Yeni (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2021)
This Community Service (P2M) activity aims to improve young women's health in the health sector, to improve the health of young women, especially reproductive health. One of the problems faced by adolescents is the lack of knowledge about health, especially reproductive health. Efforts to increase understanding of reproduction are by providing education. Counseling on reproductive health and nutrition for young women has given in basic nutrition subjects, which are adaptive in Vocational High Schools (SMK) in Catering expertise. The method used is by providing lectures, discussions, and evaluation of activities. The review has carried out by distributing a satisfaction questionnaire to P2M activities consisting of 10 statements. P2M was conducted at SMK Negeri 33 Jakarta online in the subject of Nutrition Science by involving the principal, vice-principal, 57 female students, three civil servant teachers, and four P2M Faculty members Engineering team. Activities will have held on Monday, 10 August 2020, from 07:30 to 10:00 WIB. The counseling material provided was beautiful to the participants, seen from the whole questionnaire items' average result that they were delighted with 59.4% and 37.5% expressed satisfaction. Thus the P2M activity on improving the degree of reproductive health and nutrition is beneficial for participants.